PENGARUH PERSISTENSI BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP KEGIATAN MUHADHARAH SISWA SMP MUHAMMADIYAH 14 PACIRAN: PENGARUH PERSISTENSI BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP KEGIATAN MUHADHARAH SISWA SMP MUHAMMADIYAH 14 PACIRAN - Nur Kholis (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
ABSTRACT This research aims to determine the effect of persistence in learning Islamic Religious Education (PAI) on the muhadharah activities of Muhammadiyah 14 Paciran Middle School students. This type of research is quantitative research using a sample size of 53 students. The instrument used is a multiple choice questionnaire and a correlation technique using product moment. The research results show the calculated r value is 0.549. The medium or sufficient category has a calculated r value in the range of 0.40 – 0.70 with a KD of 30.14%, while the KD of 69.86% is influenced by other factors. Hypothesis testing in this study can be concluded that the sample size is 53, df (N-n = 53-2 = 51), r calculated 0.549 and significance level 0.05, resulting in an r table of 0.4. because the calculated r is greater than the table r at a significance level of 0.05 (0.549 > 0.271). So the result is that Ho is rejected and Ha is accepted, in other words, there is an influence of the persistence of PAI learning on the muhadharah activities of Muhammadiyah 14 Paciran Middle School students.